Innate Immune Cells in the Esophageal Tumor Microenvironment - Cui, Kele; Hu, Shouxin; Mei, Xinyu; Cheng, Min (Frontiers in Immunology, 2021)
Oesophageal cancer (EC) is one of the most common mucosa-associated tumours, and is characterized by aggressiveness, poor prognosis, and unfavourable patient survival rates. As an organ directly exposed to the risk of foodborne infection, the oesophageal mucosa harbours distinct populations of innate immune cells, which play vital roles in both maintenance of oesophageal homeostasis and immune defence and surveillance during mucosal anti-infection and anti-tumour responses. In this review, we highlight recent progress in research into innate immune cells in the microenvironment of EC, including lymphatic lineages, such as natural killer and γδT cells, and myeloid lineages, including macrophages, dendritic cells, neutrophils, myeloid-derived suppressor cells, and mast cells. Further, putative innate immune cellular and molecular mechanisms involved in tumour occurrence and progression are discussed, to highlight potential directions for the development of new biomarkers and effective intervention targets, which can hopefully be applied in long-term multilevel clinical EC treatment. Fully understanding the innate immunological mechanisms involved in oesophageal mucosa carcinogenesis is of great significance for clinical immunotherapy and prognosis prediction for patients with EC.